KINERJA PELAYANAN PUBLIK PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN (KSOP) KELAS IV BAGANSIAPIAPI - Mursalin Mursalin; Meyzi Heriyanto; Febri Yuliani (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
Abstract This study aims to find out how the performance of public services at the harbor and port authority offices (KSOP class IV Bagansiapiapi. And what are the factors that affect the performance of public services at the harbor and port authority office (KSOP) class IV Bagansiapiapi. The data analysis used is descriptive qualitative analysis recommended by Miles and Huberman (1992), namely: Data Reduction, Data Presentation, and Conclusions and Verification of Results. Data collection techniques with observation, interviews (structured and in-depth with informants), and documentation. The results of the research show that the Performance of Public Service Performance at the Port Authority and Class IV Bagansiapiapi Port Authority has been carried out as it should. of the 14 (fourteen) indicators used according to Moeheriono (2012:163), namely, there are 13 (thirteen) indicators that are good (as it should be) but there is one indicator that is not good, namely the Environmental Comfort indicator, this is related to the availability of facilities the existing facilities in the working area of the Port Authority (KSOP) Class IV Bagansiapiapi office, namely Haling Island, Sinaboy and BuluHala. And the factors that affect the performance of public services at the Port Authority Port Authority Office (KSOP) class IV Bagansiapiapi are on the Individual Factor, namely Ability and Expertise, on the Psychological Factor is the Attitude, Personality and Learning and Motivation factor while the Organizational Factor is Resources, Leadership and Awards